Assessing determinant of firm value: Indonesia conventional bank analysis - Febrina Rahmi; Muhammmad Arfan; Mulia Saputra (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
The objective of this paper is to examine the factors of intellectual capital, financial leverage, institutional ownership, and working capital management (WCM) on firm value and the role of profitability as a mediator in influencing firm value. The research analysis unit focuses on the conventional banking sector on the Indonesia Stock Exchange. The panel data was taken from 28 commercial banks for five years (2016–2020), with 140 observations and data is analyzed using path analysis. Based upon the result of hypothesis testing, the study concludes that the positive correlation between profitability and firm value. Furthermore, intellectual capital, financial leverage, institutional ownership, and WCM also positively affect firm value and profitability. Based on data analysis using path analysis by comparing the path coefficient substructure, the results show that profitability acts as a mediator the effect of intellectual capital, financial leverage, institutional ownership, and WCM on firm value.